Comparison of surface aspects of turned and anodized titanium dental implant, or abutment material for an optimal soft tissue integration. Issue 8 (August 2022) - Mühl, Attila; Szabó, Péter; Krafcsik, Olga; Aigner, Zoltán; Kopniczky, Judit; Ákos Nagy,; Marada, Gyula; Turzó, Kinga
Abstract: Objectives: Soft tissue integration of dental implants lags behind natural biological integration of teeth mainly because of non-optimal surface features. Peri-implant infections resulting in loss of supporting bone jeopardize the success of implants. Our aim was to compare an anodized surface design with a turned one for a more optimal surface. Methods: Morphological and chemical structures of turned and anodized Ti surfaces (grade 5: Ti6Al4V) discs were examined by scanning electron microscopy (SEM-EDS), energy dispersive X-ray spectroscopy (EDS), and atomic force microscopy (AFM). The hydrophilic or hydrophobic features of the surfaces were determined by dynamic contact angle measurement. Results: SEM and AFM revealed significant differences in the morphology and roughness (Ra ) of the samples. Anodized discs presented a granular structure, while turned ones had circular grooves. The roughness was significantly higher for the anodized samples compared to the turned ones. XPS and EDS confirmed typical elements for both Ti6Al4V samples. Due to anodization, the amount of Ti (IV) had increased and Ti (III) had decreased in the thicker oxide layer. Anodized samples resulted in a more hydrophilic surface than the turned ones. Significance: The results suggest that the tested anodized samples present optimal surface characteristics to be used as abutment material for an optimal soft tissue integration. Highlights: Optimization of soft tissue barrier is a crucial factor in long-term dental implant success and peri-implant health. The applied anodization is an easy-to-use process to change the color of titanium to a more favorable yellow. Changes in surface morphology and hydrophilic features were favorable for soft tissue attachment. Anodized samples presented optimal surface composition to be used as abutment material of dental implants. Abstract : Titanium dental implant; turned surface; anodization; gingival attachment; roughness; chemical composition; contact angle.